Whales and Dolphins - "Okaley, Mark" (Ladybird: Loughborough, 1995)
Explains how whales and dolphins swim, dive and feed, how they are designed for and adapted to their environment, how they use each of their senses, and where they are found. It also features a gatefold, which opens up to show how the blue whale grows to such huge lengths.
Keywords: Text -- Discovery